Respuesta :

Answer:

I know i'm late but I think this might be right, I don't know, I used a website-

Step-by-step explanation:

When

√x-1

STEP

1

:

Isolate the square root on the left hand side

    Radical already isolated

    √x-1 = 0

STEP

2

:

Eliminate the radical on the left hand side

    Raise both sides to the second power

    (√x-1)2 = ()2

    After squaring

    x-1 =

STEP

3

:

Solve the linear equation

    Rearranged equation

    x -1 = 0

    Add  1  to both sides

    x = 1

    A possible solution is :

    x = 1

STEP

4

:

Check that the solution is correct

    Original equation

    √x-1 =

    Plug in 1 for  x

     √(1)-1 =

     Simplify

     √0 = 0

     Solution checks !!

    Solution is:

     x = 1

also, want to talk and be friends?

       ~Dreamer1331~

ACCESS MORE